2011
DOI: 10.1186/1756-0500-4-370
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling novel genes upregulated by both rhBMP2 and rhBMP7 during early osteoblastic transdifferentiation of C2C12 cells

Abstract: FindingsWe set out to analyse the gene expression profile of pre-osteoblastic C2C12 cells during osteodifferentiation induced by both rhBMP2 and rhBMP7 using DNA microarrays. Induced and repressed genes were intercepted, resulting in 1,318 induced genes and 704 repressed genes by both rhBMP2 and rhBMP7. We selected and validated, by RT-qPCR, 24 genes which were upregulated by rhBMP2 and rhBMP7; of these, 13 are related to transcription (Runx2, Dlx1, Dlx2, Dlx5, Id1, Id2, Id3, Fkhr1, Osx, Hoxc8, Glis1, Glis3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 62 publications
2
16
0
Order By: Relevance
“…This discrepancy might be due to two different cell types being used. Consistent to our observations, a more recent study has also shown that HtrA1 is up-regulated by BMP2 and BMP7 during osteoblastic differentiation of C2C12 cells [15]. Nevertheless, our studies extended previous findings [7] to show that osteoclast-derived HtrA1 has an inhibitory effect on osteoblast differentiation and gene expression, in addition to its effect on osteoblast mineralization process.…”
Section: Discussionsupporting
confidence: 93%
“…This discrepancy might be due to two different cell types being used. Consistent to our observations, a more recent study has also shown that HtrA1 is up-regulated by BMP2 and BMP7 during osteoblastic differentiation of C2C12 cells [15]. Nevertheless, our studies extended previous findings [7] to show that osteoclast-derived HtrA1 has an inhibitory effect on osteoblast differentiation and gene expression, in addition to its effect on osteoblast mineralization process.…”
Section: Discussionsupporting
confidence: 93%
“…GLIS1 encodes for a GLI-related Kruppel-like zinc finger transcription factor and can effectively promote the reprogramming of somatic cells during induced pluripotent stem cells (iPSC) generation (Maekawa and Yamanaka, 2011, Maekawa et al, 2011). Importantly, GLIS1 is upregulated during the osteoblastic differentiation (Bustos-Valenzuela et al, 2011) and has been linked to coronary artery calcified plaque (Divers et al, 2013), which is closely related to osteoblastic differentiation and activity (Doherty et al, 2003). Together, these results suggest that GLIS1 expression is likely to be tightly regulated in osteoblasts and cell type-specific DNA methylation may help to achieve this fine-tuning of expression.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the identification of new factors required for chromatin dynamics and organization can expand our understanding of mechanisms underpinning developmental diseases. Several studies implicate CFDP1, the human ortholog of YETI, in osteogenesis and craniofacial development (Diekwisch et al, 1999;Diekwisch et al, 2002;Thisse, 2004;Wu et al, 2008;Bustos-Valenzuela et al, 2011;Makeyev and Bayarsaihan, 2011). Future research can provide a better understanding of BCNT protein functions in chromatin organization and yield more insight into their role in developmental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…First, the mouse BCNT protein, called CP27 or CFDP1, plays essential cellular functions and is required for teeth and bone development (Diekwisch et al, 1999;Diekwisch et al, 2002). Second, in mouse, downregulation of the Cfdp1 gene correlates with the induction of cleft palate due to persistent expression of the PAX3-encoding gene in neural crest cells (Wu et al, 2008); upregulation of Cfdp1 was also observed after experimentally induced osteodifferentiation (Bustos-Valenzuela et al, 2011). Third, the Zebrafish BCNT gene, called Rltpr, is developmentally expressed in the branchial arches that will give rise to the craniofacial structures (Thisse, 2004).…”
Section: Introductionmentioning
confidence: 99%